1988
DOI: 10.1038/336068a0
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors activate the arachidonic acid cascade system in striatal neurons

Abstract: Receptors for excitatory amino-acid transmitters on nerve cells fall into two main categories associated with non-selective cationic channels, the NMDA (N-methyl-D-aspartate) and non-NMDA (kainate and quisqualate) receptors. Special properties of NMDA receptors such as their voltage-dependent blockade by Mg2+ (refs 3, 4) and their permeability to Na+, K+ as well as to Ca2+ (refs 5, 6), have led to the suggestion that these receptors are important in plasticity during development and learning. They have been im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
257
4
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 592 publications
(278 citation statements)
references
References 28 publications
15
257
4
2
Order By: Relevance
“…On the other hand, the ability of chronic LiCl to potentiate k* responses in rats to the muscarinic M 1,3,5 receptor agonist, arecoline (Basselin et al, 2003), is consistent with reports that cholinomimetics can be therapeutic as well (Bunney and Garland-Bunney, 1987;Bymaster and Felder, 2002). These published data, and the data of this study, suggest that lithium acts in BD by rectifying several neurotransmitter-signaling imbalances through downregulating NMDAR and D 2 -like receptor signaling and upregulating M 1,3,5 receptor signaling involving PLA 2 and the AA cascade (Bunney and Garland-Bunney, 1987;Bymaster and Felder, 2002;Dumuis et al, 1988;Rapoport and Bosetti, 2002;Shimizu and Wolfe, 1990).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, the ability of chronic LiCl to potentiate k* responses in rats to the muscarinic M 1,3,5 receptor agonist, arecoline (Basselin et al, 2003), is consistent with reports that cholinomimetics can be therapeutic as well (Bunney and Garland-Bunney, 1987;Bymaster and Felder, 2002). These published data, and the data of this study, suggest that lithium acts in BD by rectifying several neurotransmitter-signaling imbalances through downregulating NMDAR and D 2 -like receptor signaling and upregulating M 1,3,5 receptor signaling involving PLA 2 and the AA cascade (Bunney and Garland-Bunney, 1987;Bymaster and Felder, 2002;Dumuis et al, 1988;Rapoport and Bosetti, 2002;Shimizu and Wolfe, 1990).…”
Section: Discussionsupporting
confidence: 88%
“…NMDAprovoked EPLA 2 activation has been demonstrated in rat hippocampal slices, where it could be blocked by a specific cPLA 2 inhibitor and was accompanied by the formation of lyso-phosphatidylcholine and glycerophosphocholine, consistent with activation of the AA-selective cPLA 2 (Dennis, 1994;Weichel et al, 1999). Other studies also reported that Ca 2 + -mediated activation of PLA 2 in neurons released AA following NMDA (Dumuis et al, 1988;Lazarewicz et al, 1990;Pellerin and Wolfe, 1991;Tapia-Arancibia et al, 1992). Although both cPLA 2 and sPLA 2 were activated in some of those studies (Kim et al, 1995), it is likely that mainly cPLA 2 was activated in ours, as cPLA 2 is sensitive to the low Ca 2 + concentrations, 300 nM to 1 mM (Clark et al, 1995;Ismailov et al, 2004) that occur during normal neuronal activation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is consistent with a low abundance of DA synapses compared with a high (70%) abundance of glutamatergic synapses in rat brain (Fonnum, 1984;Raichle and Gusnard, 2002). Thus, baseline values of k* for AA in rat brain are decreased 20% to 50% following administration of MK-801, which blocks Ca 2 + -mediated activation of cPLA 2 via the ionotropic NMDA receptor (Basselin et al, 2005a;Dumuis et al, 1988;Weichel et al, 1999).…”
Section: Discussionsupporting
confidence: 77%